SPEECH STYLE OF THE MAIN CHARACTER IN THE HOBBIT: THE DESOLATION OF SMAUG MOVIE - Utama, Mappagiling Abdi; Abdullah, Abdullah (ELITERATE : Journal of English Linguistics and Literature Studies, 2022)
Speech styles are variations of standard speech that are used by individuals when they converse with one another. The purpose of this research is to determine the manner of speech that the main characters use and to describe the factors that affect those characters, specifically Bilbo Baggins and Thorin Oakenshield. In this particular study, the qualitative research method was utilized. A movie with the title The Hobbit: The Desolation of Smaug was used as the primary source of information for this study. According to the findings of the research, both Bilbo and Thorin employ one of three distinct styles, namely the formal style, the consultative style, and the casual style. The consultative mode of communication is the most prominent one utilized by Bilbo, whereas the casual mode of communication is the most prominent mode utilized by Thorin. According to Joos's theory, there are five styles; however, the research could not find evidence of two of these styles, which Joos refers to as the Frozen Style and the Intimate Style.